Optical Coherence Tomography and Visual Evoked Potentials as Prognostic and Monitoring Tools in Progressive Multiple Sclerosis - Guerrieri, Simone; Comi, Giancarlo; Leocani, Letizia (Frontiers in Neuroscience, 2021)
Understanding the mechanisms underlying progression and developing new treatments for Progressive Multiple sclerosis (PMS) are among the major challenges in the field of central nervous system demyelinating diseases. Over the last 10 years, also because of some technological advances, the visual pathways have emerged as an useful platform to study the processes of demyelination/remyelination and their relationship with axonal degeneration/protection. The wider availability and technological advances in optical coherence tomography (OCT), has allowed to add information on structural neuroretinal changes, in addition to functional information provided by visual evoked potentials (VEPs). The present review will address the role of the visual pathway as a platform to assess functional and structural damage in MS, focusing in particular on the role of VEPs and OCT, alone or in combination, in the prognosis and monitoring of PMS.